Mechanisms of diabetic nephropathy: old buddies and newcomers part 2 - Nawroth, Peter Paul; Isermann, Berend (Experimental and clinical endocrinology & diabetes, 2010)
Thieme E-Books & E-Journals
Gesehen am 08.05.2023